Effect of mechanical stimulation on tissue heterotopic ossification: an in vivo experimental study - Zhu, Zhengya; He, Zhongyuan; Tang, Tao; Wang, Fuan; Chen, Hongkun; Zhou, Jiaxiang; Lin, Chengkai; Chen, Guoliang; Wang, Jianmin; Li, Jianfeng; Liu, Xizhe; Zhou, Zhiyu; et al. (Frontiers in Physiology, 2023)
Heterotopic ossification of tendons and ligaments (HOTL) is a common clinical condition characterized by the absence of discernible features and a lack of effective treatment. Ossification of the posterior longitudinal ligament (OPLL) and tendon ossification are disabling conditions frequently associated with HOTL. In vitro experiments have demonstrated that mechanical stimulation can induce cell differentiation toward osteogenesis, thereby promoting heterotopic ossification. However, there is a scarcity of in vivo experiments describing this phenomenon.Currently, there are few experimental designs aimed at inducing ligament stretching in mice, and the mechanism of heterotopic ossification may not entirely mirror that observed in clinical cases.Therefore, there is an urgent imperative to develop a novel and feasible animal model. In this study, we utilized mice with Enpp1 gene deficiency (a mouse model with heterotopic ossification of 批注 [Editor2]: Your document was edited for correct English language, grammar, punctuation, and phrasing. In addition, we have made some changes to ensure consistency throughout the document. These changes are based on our extensive knowledge of what journals typically require. If you would like more details, please contact our Support team.